(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
Service quality has become an important tool in the service industry. Customer satisfaction is widely acknowledged as a significant differentiator that plays a crucial role in marketing both in theory and practise and serves as the primary result of any marketing effort.. This study aims to comprehend the disparity between the service quality provided by ICICI Bank and State Bank of India. SERVQUAL model which was proposed by Parasuram et al. is used to measure the service quality perceived by the customers of the state bank of India and ICICI bank in Ambala city, a city in Haryana and a state in India. The information as gathered from the different customers of the both banks VizICICI Bank and State Bank of India To get honest feedback on the level of service provided by banks, 40 respondents from each bank were personally contacted. The data demonstrates unequivocally that, when compared to ICICI Bank, there is a wide perceptual difference among State Bank of India regarding overall service quality with their respective customers, however there is a tiny perceptual difference in ICICI Bank.